Research in global citizenship education - Harshman, Jason; Augustine, Tami; Merryfield, Merry M., 1945- (Research in social education., 2015)
Globalization is changing what citizens need to know and be able to do by interrupting the assumption that the actions of citizens only take place within national borders. If our neighborhoods and nations are affecting and being affected by the world, then our political consciousness must be worldminded. The outcomes of globalization have led educators to rethink what students need to learn and be able to do as citizens in a globally connected world.This volume focuses on research that examines how K-12 teachers and students are currently addressing the challenge of becoming citizens in a globally interconnected world. Although there is an extensive body of literature on citizenship education within national contexts and a growing literature on global education, this volume offers research on the work educators are doing across multiple countries to bring the two fields together to develop global citizens.